Hubungan Asupan Serat Terhadap Kadar Glukosa Darah Pasien Rawat Jalan Diabetes Mellitus Tipe IIDi RSUD Dr. Moewardi - Lukita Sari, Andryas, Elida Soviana, S.Gz., M.Gizi, Nur Lathifah Mardiyati, S.Gz., M.S (2015)
Introduction : Diabetes mellitus is one of metabolic diseases characterized by high blood glucose levels (hyperglycemia) that occurs as a result of impaired insulin secretion, decreased insulin action, or both. One way to control diabetes mellitus is by controling blood glucose levels. One of factors that affect blood glucose levels is the intake of food include fiber intake. Objective : This study aimed to determine the relationship between fiber intake and blood glucose level in outpatients with diabetes mellitus type II at Dr.Moewardi hospital. Methods : This study was an observational study with cross-sectional design. Intake of fiber data were obtainel using a 24-hour food recall for 4 days which were not consecutive. The statistical tests used Pearson correlation tests. Results : Most respondents had low intake of fiber (69.1%) and high blood glucose level (76.4%). The correlation test showed P value of 0.039. Conclusion : There was a relationship between fiber intake and blood glucose level in outpatients with diabetes mellitus type II at Dr. Moewardi hospital Research suggestion : Patients of diabetes mellitus are, expected to improve their fiber intake to control blood glucose lavel. For hospital Dr. Moewardi expected to further improve nutritional counseling services on the diet of diabetes mellitus patients.